2022
DOI: 10.1590/1980-5373-mr-2021-0385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Commercial Mouthwashes on the Corrosion Behaviour of Dental Alloy

Abstract: Dental alloys are widely used in fabrication of removable partial dentures, particularly as a dental framework. The present study aimed at studying the effect of the commercial mouthwashes on the corrosion behavior of the Co−Cr dental casting alloy. Corrosion behavior was investigated in alcoholfree and alcohol-containing mouthwashes added to artificial saliva solutions at room temperature by electrochemical tests recorded the open circuit potential (OCP) and current density, after the surface analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…CoCrMo alloys have been widely used in dentistry for many years for partial dentures, replacing gold alloys [22][23][24][34][35][36][37][38][39]. During prosthetic and clinical treatment, one of the most important aspects is the precision of the reconstruction.…”
Section: Scanning Kelvin Probe Study Of the Cocrmo Alloy Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…CoCrMo alloys have been widely used in dentistry for many years for partial dentures, replacing gold alloys [22][23][24][34][35][36][37][38][39]. During prosthetic and clinical treatment, one of the most important aspects is the precision of the reconstruction.…”
Section: Scanning Kelvin Probe Study Of the Cocrmo Alloy Surfacementioning
confidence: 99%
“…Clinical studies show that the proper reconstruction of the tooth crown guarantees durability and prevents the infiltration of bacteria into the tissues [34]. Research shows that, in CoCrMo alloys, metal ions constituting the alloy components are released into the body to a small extent, even in an acidic environment [35][36][37][38]. CoCrMo alloys, particularly those used in partial dentures, are resistant to abrasion and temperature changes under artificial aging conditions, which proves that the alloy is resistant to repeated insertions and the removal of dentures [39].…”
Section: Scanning Kelvin Probe Study Of the Cocrmo Alloy Surfacementioning
confidence: 99%
“…Chlorhexidine may increase corrosion of orthodontic implants [ 143 ], although a similar effect for brackets was not observed [ 139 ]. Ethanol-containing mouthwashes are supposed to be the most aggressive to dental alloys due to increased galvanic corrosion [ 139 , 144 ].…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%
“…Therefore, it can be assumed, that smoking and alcohol intake would aggravate any side effects associated with dental alloys. Moreover, considering the effect of ethanol-based oral rinses on dental alloys [ 139 , 144 ], we may suppose that alcohol may increase corrosion and galvanic processes in the oral cavity.…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%
“…It has been shown that fluoride-containing products may increase galvanic corrosion of dental alloys [17][18][19][20]. Several experimental studies demonstrated the negative effects of ethanol-based mouth rinses [18,21], Listerine [22,23], and chlorhexidine [24]. It has been shown that alcohol-containing mouthwashes lead to an increased tendency to corrosion in the case of CoCr alloys [21].…”
Section: Introductionmentioning
confidence: 99%